(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Blessings and curses represent an important layer of expressive vocabulary in many languages, reflecting cultural values, emotional states, and social norms. This article provides a comparative stylistic analysis of blessings and curses in Uzbek and English. The study examines their linguistic structure, stylistic functions, pragmatic usage, and cultural specificity. By analyzing examples from both languages, the paper highlights similarities and differences in form, meaning, emotional coloring, and communicative intent. The research demonstrates that while blessings and curses in both languages serve expressive and evaluative functions, Uzbek expressions are more deeply rooted in religious, familial, and collectivist values, whereas English expressions often reflect individualism and metaphorical imagery. The findings contribute to contrastive linguistics, stylistics, and intercultural communication studies.